Loss and damage assessment in critical infrastructures due to extreme events. (March 2022) - Urlainis, Alon; Ornai, David; Levy, Robert; Vilnay, Oren; Shohet, Igal M.
Highlights: A comprehensive review of eight natural and man-made extreme events is presented. Risk-Informed evaluation of critical infrastructures preparedness is carried out. Incompatible preparedness of critical infrastructures was observed. A comprehensive multi-hazard risk assessment and management framework is developed. R 4 : redundancy, robustness, resilience and relocation of the nearby population. Abstract: Critical Infrastructures such as hospitals, power stations and communication centers play a crucial role in the performance of economy and society. Over the last few decades, the number and variety of infrastructures grew rapidly and the interdependencies between them have increased. Consequently, more and more essential services depend on the continuous performance of one, two or even more critical infrastructures such as power supply, communications, etc. It is therefore critical to ensure reliable and robust performance of critical infrastructures on a continuous basis, particularly upon the occurrence of extreme events. This paper presents a review of the contemporary state of preparedness of critical infrastructures, through a comprehensive literature review of significant extreme events that occurred in the past three decades. An effort to identify the common denominators between the different extreme events was carried out in order to universalize the discussion and stimulate thought-provoking conclusions on the present conditions of critical infrastructures and their implications in terms of preparedness, risk assessment, and disaster management. The review reveals incompatibility between the increasing risk and the actual preparedness of critical infrastructure to extreme events. The potential risk is further magnified because of the high and increasing interdependencies between CIs that were observed. A comprehensive framework of multi-hazards risk assessment and management of mitigation strategies as a decision support tool is proposed in this paper.